Program Kemitraan Wilayah (PKW) Kecamatan Kedungkandang: Peningkatan Pendapatan Keluarga Melalui Budi Daya Tanaman Nanas - Eko Yuni Prihantono; Agus Suprapto; Noermijati Noermijati (Jurnal ABM Mengabdi, 2018)
The socio-economic conditions of Kedungkandang Subdistrict especially Kedungkandang Sub-District and Buring Sub-District as relatively disadvantaged areas in Malang City become relevant as a target area to be developed into a more developed area of awareness about their education, health and environment as well as their social economy When agriculture is still the economic foundation of the community but still fails to improve welfare, efforts to increase added value for agricultural commodities are one of the solutions that need to be tried. Pineapple cultivation is chosen because these plants do not require intensive care and pineapple processed products in semi-finished and finished goods are common in the community so they can be marketed and increase family income.